2019
DOI: 10.1155/2019/2935942
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characteristics of Mn@ Cu3(BTC)2 for Low-Temperature Catalytic Reduction of NOx with NH3

Abstract: Novel catalysts with high activity for the selective catalytic reduction of NO with NH3 (NH3-SCR) at low temperatures are highly demanded. In this study, mixed-node metal-organic frameworks (MOFs), e.g. Mn@CuBTC with controlled Mn composition in Cu3(BTC)2, were fabricated using postsynthetic exchange method and their structural characteristics and catalytic performances for NH3-SCR reaction were assessed. A series of analyses in terms of structure, surface morphology, texture, and chemical state determined tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…DRIFTS experiments were performed showing that NH 3 is adsorbed on Lewis sites, and no peaks corresponding to NO were observed. The authors suggest that the combination of proper pore sizes, enhancement of redox activity via incorporation of Mn 4+ ions, and the synergistic effect between Mn 2+ and Cu 2+ results in superior DeNO x performance . The commercial HKUST-1 (Basolite C300) was examined under NH 3 -SCR conditions in the studies of Świrk et al , During the pretreatment step carried out in helium from 145 to 250 °C, the authors observed a gradually increasing formation of carbon dioxide with a heating ramp, highlighting the crucial role of the temperature.…”
Section: Catalytic Reduction Of No Xmentioning
confidence: 99%
See 1 more Smart Citation
“…DRIFTS experiments were performed showing that NH 3 is adsorbed on Lewis sites, and no peaks corresponding to NO were observed. The authors suggest that the combination of proper pore sizes, enhancement of redox activity via incorporation of Mn 4+ ions, and the synergistic effect between Mn 2+ and Cu 2+ results in superior DeNO x performance . The commercial HKUST-1 (Basolite C300) was examined under NH 3 -SCR conditions in the studies of Świrk et al , During the pretreatment step carried out in helium from 145 to 250 °C, the authors observed a gradually increasing formation of carbon dioxide with a heating ramp, highlighting the crucial role of the temperature.…”
Section: Catalytic Reduction Of No Xmentioning
confidence: 99%
“…The authors suggest that the combination of proper pore sizes, enhancement of redox activity via incorporation of Mn 4+ ions, and the synergistic effect between Mn 2+ and Cu 2+ results in superior DeNO x performance. 114 The commercial HKUST-1 (Basolite C300) was examined under NH 3 -SCR conditions in the studies of S ́wirk et al 115,116 During the pretreatment step carried out in helium from 145 to 250 °C, the authors observed a gradually increasing formation of carbon dioxide with a heating ramp, highlighting the crucial role of the temperature. The temperature of 185 °C is recognized as the highest possible and carbon-free experimental adjustment, allowing the authors to prevent a partial decomposition of the organic framework.…”
Section: Selective Catalytic Reduction Process (Scr)mentioning
confidence: 99%
“…Ion exchange is one of the most effective methods for synthesizing bimetallic MOFs. Yao et al first synthesized Cu-MOF and then incorporated Mn ions into the Cu-MOF through ion exchange in order to obtain Mn/Cu-BTC (BTC = 1,3,5-benzenetricarboxylic acid) [23]. The introduction of Mn changed the pore size of the Cu-MOF, and the synergistic effects of Mn and Cu enhanced its redox activity.…”
Section: Bimetallic Mofs As No X Scr Catalystsmentioning
confidence: 99%
“…Therefore, the increased acidic sites might represent one of the most important reasons for the higher catalytic activity of the MnO x -Cu/AC catalyst. Yao et al found that the synergistic effects between Mn and Cu ions could further enhance the low-temperature performances via modified active sites [48]. Moreover, Shu et al found that surface acidity played a critical role in the SCR reaction [49].…”
Section: The Catalytic Activity Analysis Of the Scr Catalystmentioning
confidence: 99%